2018
DOI: 10.1080/03055698.2018.1446326
|View full text |Cite
|
Sign up to set email alerts
|

How do self-efficacy beliefs for academic writing and collaboration and intrinsic motivation for academic writing and research develop during an undergraduate research project?

Abstract: van den Berg a and Paul W. van den Broek b a leiden university Graduate School of teaching (iclon), leiden, the netherlands; b institute of Pedagogical Sciences, leiden university, leiden, the netherlands ABSTRACT Research skills are important for university graduates, but little is known about undergraduates' motivation for research. In this study, self-efficacy beliefs and intrinsic motivation for several research activities were measured three times during an undergraduate research project (N = 147 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 42 publications
3
34
0
6
Order By: Relevance
“…Besides task complexity, interdependence is another factor to consider when investigating task characteristics. Interdependence exists when group members believe they can only reach their goals when the other group members also reach their goals (Johnson and Johnson 2009;Van Blankenstein et al 2019). There are two common types of interdependence, namely outcome interdependence and means interdependence (Bertucci et al 2016).…”
Section: Task Characteristicsmentioning
confidence: 99%
“…Besides task complexity, interdependence is another factor to consider when investigating task characteristics. Interdependence exists when group members believe they can only reach their goals when the other group members also reach their goals (Johnson and Johnson 2009;Van Blankenstein et al 2019). There are two common types of interdependence, namely outcome interdependence and means interdependence (Bertucci et al 2016).…”
Section: Task Characteristicsmentioning
confidence: 99%
“…More specifically, at university levels, the relationship has been determined between writing self-efficacy and other motivational dimensions such as anxiety [45,53], attitudes towards writing [54,55], apprehension and beliefs [42,56,57], intrinsic, extrinsic motivation and effort [58,59]. In addition, the reviews on regression analysis show that writing self-efficacy is an independent variable for predicting writing achievement [60].…”
Section: Writing Self-efficacymentioning
confidence: 99%
“…Although there is no complete agreement when it comes to identifying the dimensions of "writing self-efficacy", there is a consensus on its involvement with metacognitive self-regulatory processes, which justifies its inclusion in programs that seek to improve the quality of academic texts [28,58,59,67]. However, the diversity of results in these investigations highlights the need to base didactic interventions according to the real relationships between the different factors that are intended to be promoted.…”
Section: Writing Self-efficacymentioning
confidence: 99%
“…Studies that have analyzed the influence of internal motivation in academia showed that it is positively related to adaptive behaviors [ 18 ], academic performance [ 19 ], metacognitive processes [ 20 ], and critical thinking [ 20 ]. Conversely, external motivation and amotivation showed to be positively related to school dropout [ 21 ], stress [ 22 ], and exam failure [ 23 ].…”
Section: Introductionmentioning
confidence: 99%